Das Rechtsverhältnis zwischen Schiedsorganisation und Schiedspartei Rechtsgrundlagen, Verfahrensgarantien und Konfliktfälle - Wahnschaffe, Christian Johannes (Mohr Siebeck, 2023)
Arbitral institutions perform a key role in administering legal disputes. Still, many aspects of the legal relationship to arbitral institutions remain unresolved and disputed. This book systematises the contractual legal foundation, the domestic and international legal sources that bind arbitral institutions to standards of due process and neutrality as well as the legal parameters that apply to potential conflicts and judicial intervention.
PublicationDate: 20240312
Keywords: Schiedsgerichtsbarkeit -- Streitbeilegung -- Schiedsverfahren -- Arbitration -- Bibeldidaktische Konzepte -- Schiedsinstitution -- Prodemokratische Interventionen -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Zivilverfahrensrecht, Insolvenzrecht